2023
DOI: 10.3389/fpubh.2023.1099552
|View full text |Cite
|
Sign up to set email alerts
|

Exploring HPV vaccination policy and payer strategies for opportunities to improve uptake in safety-net settings

Abstract: IntroductionWe explored priorities and perspectives on health policy and payer strategies for improving HPV vaccination rates in safety-net settings in the United States.MethodsWe conducted qualitative interviews with policy and payer representatives in the greater Los Angeles region and state of New Jersey between December 2020 and January 2022. Practice Change Model domains guided data collection, thematic analysis, and interpretation.ResultsFive themes emerged from interviews with 11 policy and 8 payer part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
(37 reference statements)
0
1
0
Order By: Relevance
“…We have previously reported policy level strategies for improving HPV vaccination, such as raising awareness about minor consent policies in states where applicable. 47 However, we found that funding sources for HPV vaccination often did not benefit medically underserved adolescents, which could create tension when minors consent to getting the HPV vaccine for themselves in SBHCs in some states. For example, in July 2022 shortly after we finished interviews and focus groups, the Family PACT program, which covers reproductive health education and services in California, including programs within SBHCs, changed its policy to cover the HPV vaccine for adults between ages 19–45, but not for adolescents.…”
Section: Discussionmentioning
confidence: 83%
“…We have previously reported policy level strategies for improving HPV vaccination, such as raising awareness about minor consent policies in states where applicable. 47 However, we found that funding sources for HPV vaccination often did not benefit medically underserved adolescents, which could create tension when minors consent to getting the HPV vaccine for themselves in SBHCs in some states. For example, in July 2022 shortly after we finished interviews and focus groups, the Family PACT program, which covers reproductive health education and services in California, including programs within SBHCs, changed its policy to cover the HPV vaccine for adults between ages 19–45, but not for adolescents.…”
Section: Discussionmentioning
confidence: 83%
“…In some countries, this authority is clearly defined, while in others, it may be subject to interpretation or legal challenges [ 32 ]. It is important to navigate these legal considerations and ensure that the mandate is implemented within the boundaries of the law [ 47 ].…”
Section: Reviewmentioning
confidence: 99%